2018
DOI: 10.3389/fevo.2018.00138
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral Hybridization Yields Evolutionary Distinct Hybrids Lineages and Species Boundaries in Crocodiles, Posing Unique Conservation Conundrums

Abstract: Interspecific hybridization can lead to adaptation and speciation, especially in the context of recent radiations. The emblematic Crocodylus (true crocodiles) is the most broadly distributed, ecologically diverse, and species-rich crocodylian genus. Nonetheless, their within-species evolutionary processes are poorly resolved mainly due to their potential for hybridization. Notably, the evolutionary outcomes when hybridization is ancient and involves long-lived species, like crocodiles, remain largely unexplore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 69 publications
0
35
2
Order By: Relevance
“…As a widespread species living across a diversity of fresh and brackish water habitats, able to move long distances across saltwater, the American crocodile has been often considered "homogenous" across its range. With most research focusing on hybrid zones (6,8,11,16,34), our study contributes to current debates on the taxonomic complexity of C. acutus (25,35) Overall, our findings improve our understanding of populations of C. acutus across seven countries and provide sound evidence of genetic structuring with direct consequences into management of local, unique populations.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…As a widespread species living across a diversity of fresh and brackish water habitats, able to move long distances across saltwater, the American crocodile has been often considered "homogenous" across its range. With most research focusing on hybrid zones (6,8,11,16,34), our study contributes to current debates on the taxonomic complexity of C. acutus (25,35) Overall, our findings improve our understanding of populations of C. acutus across seven countries and provide sound evidence of genetic structuring with direct consequences into management of local, unique populations.…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, future studies should aim at using whole-genome sequencing to resolve population structuring further and to understand the phylogenetic evolution of the American crocodile and its relationships with other crocodilian species in the Americas and the Insular Caribbean. Finally, as research looks deeper into C. acutus lineages across its range and suggests the occurrence of potential cryptic species as a result of ancient hybridization and other evolutionary processes (25,35) our study aims at providing population-level data to inform current management and conservation as we continue our debate into C. acutus species designations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These clusters are usually defined considering habitat types within the species range, local conservation status, threats, enforcement, and legislation [19,31], as well as patterns of genetic variation within and among subpopulations. The majority of the work on C. acutus genetic variation has focused on zones where it can hybridize in the wild with C. rhombifer and C. moreletti [7,9,12,13,32,33]. Though information about genetic differentiation has been used as a tool for delineating local management units on some species of Crocodylus [34], there is still a need to incorporate population-level genetic information into conservation planning for many species of crocodilians, including the American crocodile.…”
Section: Introductionmentioning
confidence: 99%
“…C. acutus populations along the Pacific coast of Costa Rica exhibited small to moderate levels of inbreeding and significant levels of population differentiation potentially attributed to the lack of connectivity between some localities and the occurrence of population bottlenecks in the past [37]. In addition, Pacheco et al [33] extensive sampling throughout Mexico revealed several unique lineages as a result of historical and present hybridization between C. acutus and C moreletti. In parallel to C. acutus' species designation debates [33,36], it is imperative to strengthen the comparative research of extant populations to inform local and regional management and incorporate lacking information into the broader species assessment.…”
Section: Introductionmentioning
confidence: 99%